Culture-Sensitive Public Procurement Benchmarking - Fabrègue, Brian F.; Portal, Léo J. (Journal of Infrastructure Policy and Management (JIPM), 2021)
In this brief we will address the measure of managing public procurement taking into consideration cultural, corporate and organizational specificities, with a sustainable development strategy in mind. When such tools are used in conjunction, the efficiency of production applications is increased. Further research should focus on the investigation of foreign markets for industrial and state businesses’ public procurement, including private law state-owned companies, as well as on developing a mechanism to evaluate public procurement that takes economic, social, and environmental factors into account. Finally, we need to be aware that integrating cultural factors when dealing with public procurement is fundamental when it comes to leadership issues. Underpinning leadership is an ability to comprehend people, their values, and characteristics, and how these factors may correct and adapt public procurement methodology.